Bryophytes as Indicators of Disturbance in One of the Last Remnants of the Mountain Forests of El Oro Province, Ecuador - Ángel Benítez; Richard Nagua; Jefferson Medina; Gregorio Lapo; Erika Yangua-Solano; Rolando Andrade-Hidalgo (Plants)
Epiphytic bryophytes are an important component in terms of the diversity and functioning of montane forests known as biodiversity hotspots. Bryophytes are highly dependent on their external environments because they are sensitive to environmental changes related to disturbance, fragmentation, air pollution, and climate change. The richness and composition of bryophytes in remnants of primary and secondary forests were analyzed, where the richness and cover were recorded on trunk bases of 120 trees. Changes in species richness and diversity were analyzed using generalized linear models (GLMs), and changes in species composition, using multivariate analysis. A total of 57 bryophyte species (36 liverworts and 21 mosses) were recorded in trunk bases. For the first time, 19 new liverworts for the province of El Oro are reported. The richness and diversity of bryophyte species decrease in disturbed forests when compared to primary forests, with a marked decrease in species less adapted to conditions of high light (shade epiphytes). In the same line, species composition is different in each type of forest, where bryophytes with high humidity requirements were abundant in primary forests. This study confirms that forest disturbance is a key factor in determining not only the number of species but also the composition of bryophyte species. The maximum tree diameter and primary forest remnants are important factors in the conservation of sensitive bryophyte species at the base of trees in one of the last remnants of mountain forests in El Oro Province, Ecuador.